KAJIAN AWAL PERKEMBANGAN PENELITIAN KEBUDAYAAN DI RIAU - Junaidi, Junaidi (Jurnal Ilmu Budaya, 2008)
This writing aims to describe the visionof cultural development in Riau which includes the essence of cultural research, the development of cultural research in Riau.